Hubungan Posisi Menyusui, dan Perlekatan dengan Kejadian Bendungan ASI pada Ibu Postpartum - Yudrika, Siti Zulhjjah, Titik almujahidiani, Heryanti, Filza (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2026)
Breast milk engorgement is one of the common problems experienced by postpartum mothers and can hinder the success of exclusive breastfeeding. The incidence of breast milk engorgement is influenced by several factors, including breastfeeding position, latch-on, and breast care. This study aimed to analyze the relationship between breastfeeding position, latch-on, and breast care with the incidence of breast milk engorgement in postpartum mothers. This study used a descriptive analytic design with a cross-sectional approach. The research sample consisted of 43 postpartum mothers at PMB Yulma Sastri selected using a total sampling technique. Data analysis was performed using the Chi-Square test. The results showed a significant relationship between breastfeeding position and the incidence of breast milk engorgement (p-value = 0.001) and between latch-on and the incidence of breast milk engorgement (p-value = 0.020). The breastfeeding position variable had an OR value of 12.67 and latch-on had an OR value of 5.33. Meanwhile, breast care did not show a significant relationship with the incidence of breast milk engorgement (p-value = 1.000; OR = 1.00). This study indicates that proper breastfeeding techniques, especially breastfeeding position and latch-on, play an important role in preventing breast milk engorgement in postpartum mothers.